Selection of Medical Therapy in Glaucoma Patients in the Outpatient Eye Clinic Soetomo General Academic Hospital Surabaya - Praba, Venansya Maulina; Primitasari, Yulia; Qorib, Mohammad Fathul; Loebis, Rozalina (Folia Medica Indonesiana, 2021)
Highlight: • Medical therapy selection in the outpatient eye clinic were determined. • Treatment of prostaglandin analogue therapyfor primary open angle glaucoma was the most common glaucoma type. Abstract: Glaucoma is the second leading cause of blindness and the third cause of visual impairment. Glaucoma management includes medical therapy, laser, and incisions. This study aims to determine the selection of medical therapy in the outpatient eye clinic Soetomo General Academic Hospital Surabaya. This study was a retrospective descriptive study. The variables were type of glaucoma, visual acuity, intraocular pressure, and drug therapy. Data processing was done by collecting, grouping, and describing data. Glaucoma was mostly common in 50-64 years old (37.66%), male (50.65%), most patients lived in Surabaya (53.68%), the most common type was Primary Open-Angle Glaucoma (32.90%), the most medical therapy given in the first visit in 2019 was single medical therapy (67.97%), the most single drug therapy was latanoprost (49.68%), the most drugs combination was timolol maleat with acetazolamide (35.14%), the most commonly drugs class were prostaglandin analogues (48.48%), most of the visual acuity values were 6/6 - 6/18 (1,00 – 0,33) (37.88%), most intraocular pressure was in the 11-21 mmHg (62.55%). The most common type of glaucoma was primary open angle glaucoma with the most therapy given was prostaglandin analogue.